PREDIKSI BATAS CEKUNGAN JAWA TIMUR UTARA DENGAN PEGUNUNGAN SELATAN DI DAERAH MAGETAN - PLAOSAN DENGAN METODE GRAVITASI - Wijayanti, Dewi; Yulianto, Rr. Tony; Nurwidyanto, M. Irtem (JURNAL SAINS DAN MATEMATIKA, 2009)
ABSTRACT-Geophysics investigation with the gravity method to antisipate the existence of boundary of North East Java Basin with the South Mountains in Magetan - Plaosan have been done at 2 – 11 December 2004 by using gravitymeter La Coste & Romberg type G-I177, and resulted 50 station. Data measured field is the observation gravitation position height and terrain conection for A until D zone. To obtain the complete Bouguer anomaly, reduction of field data was performed with standart correction. Bouguer density of rock is obtained 2,30 gram/cm3. Regional and residual anomaly was obtained from filtering of complete bouguer anomaly by using polynomial surface fitting. The quantitative analysis of second order residual anomaly was performed by using Grav2DC for windows. The modelling resulted Lawu lava with density 2,35 gram/cm3 and culminate deepness is 300 m, Tuf Jobolarangan with density 2,20 gram/cm3 and culminate deepness is 300 m, sediment rock with density 2,10 gram/cm3 and culminate deepness is 123,84 m, Igneous rock with density 2,70 gram/cm3 and culminate deepness is 1.721,53 m. Basin boundary marked with the exsistence of sediment rock and igneous rock in subsurface of the area. Interpretdion of modelling indicate that Magetan - Plosan area anticipated to represent the south boundary of North East Java Basin with the South Moantains. Keynotes : Gravity, terrain correction, Bougeur anomaly